Blood Pressure–Lowering Efficacy of the Fixed‐Dose Combination of Azilsartan Medoxomil and Chlorthalidone: A Factorial Study - Sica, Domenic (J Clin Hypertens (Greenwich), 2012)
J Clin Hypertens (Greenwich). 2012; 14:284–292. ©2012 Wiley Periodicals, Inc. This study compared the efficacy and safety of fixed‐dose combinations (FDCs) of the angiotensin II receptor blocker azilsartan medoxomil (AZL‐M) and the thiazide‐like diuretic chlorthalidone (CLD) with the individual monotherapies in a double‐blind factorial study. A total of 1714 patients with clinic systolic blood pressure (SBP) 160 mm Hg to 190 mm Hg inclusive were randomized to AZL‐M 0 mg, 20 mg, 40 mg, or 80 mg and/or chlorthalidone 0 mg, 12.5 mg, or 25 mg. The primary efficacy end point was change from baseline to 8 weeks in trough (hour 22–24) SBP by ambulatory blood pressure (BP) monitoring (ABPM). Patients’ mean age was 57 years; 47% were men and 20% were black. Baseline trough BP was approximately 165/95 mm Hg and 151/91 mm Hg by clinic and ABPM measurements, respectively. For the pooled AZL‐M/CLD 40/25‐mg and 80/25‐mg FDC groups, SBP reduction by ABPM at trough was 28.9 mm Hg and exceeded AZL‐M 80 mg and CLD 25 mg monotherapies by 13.8 mm Hg and 13 mm Hg, respectively (P<.001 for both comparisons). Discontinuation rates and elevations in serum creatinine were dose‐dependent and occurred more often in the AZL‐M/CLD groups. In patients with stage 2 hypertension, treatment with the combination of AZL‐M and CLD resulted in substantially greater SBP reduction compared with either agent alone.